Peningkatan Hasil Belajar Siswa Melalui Penggunaan Media Aplikasi Canva Pada Mata Pelajaran IPAS Kelas V B UPTD SDN 145 Inpres Pampangan - Nur Hikmah; Sri Rahayu; Fitri Ramadhani; Siti Aisyah Ramadhani Fitri (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This research aims to improve student learning outcomes by applying the Canva application learning media to the science and science subject class V B UPTD SDN 145 Inpres Pampangan. This research is Classroom Action Research, the subject of this research is V B, totaling 30 students consisting of 17 men and 13 women. The implementation of this action was carried out for three weeks, each week including learning and assessment. The presentation of the first cycle material starts on 14 September 2023 and the first cycle test on 18 September 2023. The presentation of the second cycle material starts on 19 September 2023 and the second cycle test is held on 23 October 2023. The results of the research show that the learning outcomes of the first cycle students are average. - average 78.33%. Then in cycle II it increased to 94.00%. The contribution of the application of the Canva application learning media to improving student learning outcomes is very significant, meaning it is in the high category. So it can be concluded that the teacher's ability to apply the Canva application learning media can improve student learning outcomes in science and science subjects in class V B UPTD SDN 145 Inpres Pampangan.